FORMAL AND INFORMAL SUBSTANCE USE TREATMENT UTILIZATION AND ALCOHOL ABSTINENCE OVER SEVEN YEARS: IS THE RELATIONSHIP DIFFERENT FOR BLACKS AND WHITES? - Avalos, Lyndsay Ammon (2011)
BACKGROUND: This study examines whether the effects of formal substance use treatment utilization and Alcoholics Anonymous (AA) on 30-day abstinence vary for black versus white Americans. METHODS: The current analysis utilizes data from a longitudinal sample of 1,013 black and white, dependent and problem drinkers across a 7-year period. Participants were identified through a probability survey in the general population and consecutive intakes in chemical dependency treatment programs in a California County. Generalized Estimating Equations assessing interactions between race and treatment utilization incorporated variables from four post-baseline interviews, controlling for baseline variables. RESULTS: Formal treatment utilization was associated with 30-day abstinence (OR:1.6, 95%CI:1.3, 2.1), yet this relationship did not differ for blacks and whites. In contrast, there was a significant interaction between AA utilization, race and 30-day abstinence. While both whites and blacks who attended AA were more likely to report 30-day abstinence compared to their non-AA attending counterparts (white OR:4.0, 95%CI:3.2–5.1 vs. black OR:2.2, 95%CI:1.5–3.2), the relationship was stronger for whites. Among those who did not attend AA, blacks were more likely than whites to be abstinent. Post-hoc analyses suggest that these latter findings may be related to greater religiosity and “drier” social networks among black Americans. CONCLUSIONS: While utilization of formal treatment may yield similar benefits for blacks and whites, AA utilization may be more important for maintaining abstinence among whites than blacks. Future research should investigate racial differences in social network drinking patterns and religious reinforcement of sobriety, and the role these may play in AA outcomes.